Pengaruh Penyuluhan dengan Media Elektronik Terhadap Tingkat Pengetahuan dan Sikap Siswa Tentang HIV/AIDS di Sma Mathla’ul Anwar Kabupaten Pandeglang (Universitas Malahayati Lampung, 2023)
ABSTRACT HIV/AIDS in adolescents remains a major problem with implications for adolescent health. Increased sexual activity among adolescents leads to HIV/AIDS due to lack of knowledge about HIV/AIDS. Objective: To determine the effect of electronic media counseling on the level of knowledge and attitudes of HIV/AIDS in students of Mathla'ul Anwar High School, Pandeglang Regency. To determine the effect of electronic media counseling on the level of knowledge and attitudes of HIV/AIDS in students of Mathla'ul Anwar High School, Pandeglang Regency. Type of quantitative research, pre-test and post-test. The sample for this study was 172 respondents. Analysis of univariate and bivariate data using t-test correlation analysis. Based on bivariate results, the study found that audio counseling had a significant effect on the level of HIV/AIDS knowledge of p-value students (0.0005), audio-visual guidance had a significant effect on students' HIV/AIDS knowledge with p value (0.0005), audio-visual counseling had a significant effect on students' attitudes towards HIV/AIDS with p value (0.0005) and there was a significant effect on HIV/AIDS students p-value (0.0005) for the effect of counseling on attitudes Audiovisual. There is an influence of counseling with audio media on the level of student knowledge about HIV/Aids, There is an influence of audio-visual counseling on students' AIDS knowledge level, there is an influence of audio counseling on students' attitudes towards HIV/AIDS, and there is an audiovisual influence on students' attitudes towards HIV/AIDS. Keywords : HIV/AIDS, Counseling, Electronic Media ABSTRAK HIV/AIDS pada remaja tetap menjadi masalah besar yang berimplikasi pada kesehatan remaja. Meningkatnya aktivitas seksual di kalangan remaja mengarah pada HIV/AIDS karena kurangnya pengetahuan tentang HIV/AIDS. Untuk mengetahui pengaruh penyuluhan media elektronik terhadap tingkat pengetahuan dan sikap HIV/AIDS pada siswa SMA Mathla'ul Anwar Kabupaten Pandeglang. Jenis penelitian kuantitatif, pre-test and post-test. Sampel untuk penelitian ini adalah 172 responden. Analisis data univariat dan bivariat menggunakan analisis korelasi uji-t. Berdasarkan hasil bivariat, penelitian menemukan bahwa konseling audio berpengaruh signifikan terhadap tingkat pengetahuan HIV/AIDS siswa p-value (0,0005), Bimbingan audio visual berpengaruh signifikan terhadap pengetahuan HIV/AIDS siswa dengan p value (0,0005), penyuluhan audio visual berpengaruh signifikan terhadap sikap siswa terhadap HIV/AIDS dengan p value (0,0005) dan ada ada pengaruh yang signifikan pada siswa HIV/AIDS p-value (0,0005) untuk pengaruh penyuluhan terhadap sikap audiovisual. Ada pengaruh penyuluhan dengan media audio terhadap tingkat pengetahuan siswa tentang HIV/Aids, Ada pengaruh penyuluhan audio visual terhadap tingkat pengetahuan AIDS siswa, ada pengaruh penyuluhan audio terhadap sikap siswa terhadap HIV/AIDS, dan ada pengaruh audiovisual terhadap sikap siswa terhadap HIV/AIDS. Kata Kunci : HIV/AIDS, Penyuluhan, Media Elektronik